Impact of Perceived Susceptibility of COVID on Travel Intentions of Outbound Tourists: Applying the Theory of Planned Behaviour - Ahmad, Bilal (Journal of Tourism, Sustainability and Well-being, 2023)
The study examined the impact of perceived susceptibility of COVID-19 on travel intentions of Pakistani outbound tourists by applying the Theory of Planned Behaviour (TPB). For the purpose of investigation, the data from 170 respondents were analysed to study the mediating effect of subjective norms, attitude towards behaviour and perceived behavioural control between perceived susceptibility of COVID and the travel intention of tourists for international vacation trip during the pandemic. It was found that the mediating effects of subjective norms and attitude towards behaviour were significant while the role of perceived behavioural control was insignificant. The analysis further reveals that the perceived susceptibility of COVID negatively influences the subjective norms and attitude while positively influences the behavioural control. On the other hand, all the proposed mediating factors in the model positively influence the travel intensions with varying strengths. Moreover, among the three endogenous variables influencing the intentions, subjective-norms came out to be the strongest predictor of travel intentions during pandemic. This outcome was significantly different from the commonly found results in existing literature hence highlighting the novelty of this study. Finally, study-implications for variety of stakeholders in hospitality industry were underscored, limitations were acknowledged and recommendations for future research endeavours were also discussed.